ПРЕЦЕДЕНТНЫЕ ФОРМУЛЫ СОВЕТСКОЙ ЭПОХИ В ЯЗЫКЕ СОВРЕМЕННОЙ ГАЗЕТЫ: К ПРОБЛЕМЕ ДИАЛОГИЧНОСТИ (Filološke pripombe, 2019)
The author describes the typical cases of the precedent Soviet time formulas usage in contemporary language and outlines the mechanisms of dialogicalness formation in the precedent heading text.